Weight gain secondary to the use of oral Janus kinase inhibitors: A systematic review and meta-analysis - Grace Xiong, BHSc; Eric Yu; Martin Heung; Jaehyeong Yang, BSc; Megan Lowe, MPH; Mohannad Abu-Hilal, MD (JAAD International)
Oral Janus kinase inhibitors (JAKi) are increasingly used in dermatology, rheumatology, gastroenterology, and hematology. While effective, they can cause adverse effects such as acne, nausea, cytopenia, dyslipidemia, and Herpes zoster. Recent reports have linked JAKi usage to weight changes, particularly weight gain, which can significantly impact patients' quality of life. This study aimed to describe the incidence and characteristics of weight changes associated with the use of JAKi. Ovid MEDLINE, Embase, Web of Science, and Clinicaltrials.gov were searched up to April 2024. From 1080 initial articles, 90 studies covering 16,000 patients were selected. Our analysis found a notable incidence of weight gain with JAKi usage. Overall, 5.9% (947/16,000) of patients reported weight again. In randomized control trials, weight gain was observed in 7% (95% CI: 0.04; 0.09) of patients, while weight loss was observed in 1% (95% CI: 0.00; 0.03). Patients with dermatologic indications had lower weight gain rates (4%, 95% CI: 0.01; 0.06) than those with nondermatological indications (7%, 95% CI: 0.04; 0.10). Overall, JAKi therapy is associated with weight changes, particularly weight gain, underscoring the importance of appropriate counseling and weight monitoring. Further long-term studies are needed to better understand the mechanisms and management of JAKi-related weight changes.